Spalling‐Induced Liftoff and Transfer of Electronic Films Using a van der Waals Release Layer. Issue 42 (20th September 2021) - Blanton, Eric W.; Motala, Michael J.; Prusnick, Timothy A.; Hilton, Albert; Brown, Jeff L.; Bhattacharyya, Arkka; Krishnamoorthy, Sriram; Leedy, Kevin; Glavin, Nicholas R.; Snure, Michael
Abstract: Heterogeneous integration strategies are increasingly being employed to achieve more compact and capable electronics systems for multiple applications including space, electric vehicles, and wearable and medical devices. To enable new integration strategies, the growth and transfer of thin electronic films and devices, including III‐nitrides, metal oxides, and 2D materials, using 2D boron nitride (BN)‐on‐sapphire templates are demonstrated. The van der Waals (vdW) BN layer, in this case, acts as a preferred mechanical release layer for precise separation at the substrate–film interface and leaves a smooth surface suitable for vdW bonding. A tensilely stressed Ni layer sputtered on top of the film induces controlled spalling fracture that propagates at the BN/sapphire interface. By incorporating controlled spalling, the process yield and sensitivity are greatly improved, owed to the greater fracture energy provided by the stressed metal layer relative to a soft tape or rubber stamp. With stress playing a critical role in this process, the influence of residual stress on detrimental cracking and bowing is investigated. Additionally, a back‐end selected area lift‐off technique is developed which allows for isolation and transfer of individual devices or arbitrary shapes. Abstract : A versatile technique for exfoliating and transferring electronic films and devices is presented. A variety of films as well as complex high‐performance devices can be transferred, paving the way for increased system performance and functionality. Film and device characterization reveal unique strain‐related challenges and solutions. This technique can potentially enable new heterogeneous integration electronics packaging strategies.